Influence of fillers and bonding agents on the viscoelasticity of highly filled elastomers. Issue 16 (19th March 2014) - Azoug, Aurélie; Nevière, Robert; Pradeilles‐Duval, Rachel‐Marie; Constantinescu, Andrei
ABSTRACT Highly filled elastomers such as solid propellants exhibit a complex nonlinear viscoelastic behavior. This work aimed at determining the influence of binder–filler and filler–filler interactions on the microstructure and the viscoelastic properties of the propellant using a design of experiments method. The influences of the filler fraction and of the filler–binder bonding agents (FBBA) were measured by swelling experiments and prestrained dynamic mechanical analyses. The results showed that FBBA react on the filler surface and concentrate the curing agents in the vicinity of the fillers. The nonlinearity of the viscoelastic behavior originated from filler–filler interactions that created high stress zones between fillers and therefore constrained the movements of the macromolecules of the binder. Filler–binder interactions induced by the FBBA increased the filler effective volume as well as the heterogeneous stress distribution in the microstructure. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40664.